2010
DOI: 10.1007/s11882-010-0155-6
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine Autoinjector Refill History in an HMO

Abstract: Epinephrine can be lifesaving in episodes of anaphylaxis, yet it is underprescribed and underused. Tracking of epinephrine refills over time for patients with a diagnosis of anaphylaxis has not been reported. This study reports on the refill history of 14,677 patients in a large HMO who received an initial dispensing of EpiPen (Dey Pharma, Basking Ridge, NJ) or EpiPen Jr between 2000 and 2006. A total of 6,776 (46%) refilled at least once. Twenty-five percent of the patients who were in the cohort for 5 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Beyond filling initial prescriptions, Kaplan et al . evaluated nearly 15,000 patients in a health maintenance organization (HMO) over a 6‐year period and found that less than 50% refilled their EAI even once and that only 11% refilled consistently at all expected refill times.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond filling initial prescriptions, Kaplan et al . evaluated nearly 15,000 patients in a health maintenance organization (HMO) over a 6‐year period and found that less than 50% refilled their EAI even once and that only 11% refilled consistently at all expected refill times.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-six percent of patients refilled their injector at least once. Refills progressively decreased each year thereafter [23]. For the above reasons, epinephrine may not be given and education about anaphylaxis and avoidance of triggers is critical for patients and caregivers.…”
Section: Barrier To Using Epinephrine Auto-injectorsmentioning
confidence: 99%
“…School-aged children (aged ≥5 years) were less likely than younger children to have their EAI with them when eating lunch (25 % vs 42 %) or a snack (28 % vs 37 %) [37•]. In a recent study of 14,677 patients who filled an initial prescription for an EAI only 46 % ever refilled the prescription (63 % for children), and only 11 % refilled it at all the expected refill times [43]. It has been shown that parental empowerment and training on the use of an EAI significantly ( P  ≤ 0.05) correlates with greater parental comfort with administration [44], and EAI-training improves the odds of having an EAI readily available [37•].…”
Section: Treatmentmentioning
confidence: 99%